The Construction of Russian Orthodoxy in Chukotka: Ministering to the People and Marking the Territory in an Arctic Border Zone - Vaté, Virginie (Archives de sciences sociales des religions, 2024)
Over the last two decades, the Russian Orthodox Church has commissioned the construction of churches and other religious monuments throughout Russia, marking the land as Orthodox. Chukotka, a region located at the extreme northeast of the country, is no exception to this general rule. Still, the extent of the construction and of other activities sponsored by the Orthodox Church in Chukotka is remarkable for a number of reasons, including the specificities of the colonial history of the region, its remoteness, sparse population, and fierce climatic conditions, and its proximity to the United States. Based on fieldwork in 2018 and on long-term experience in Chukotka since 1993, this article documents the socio-historical, ethnographic, and geopolitical aspects of the presence of the Russian Orthodox Church in the region, focusing on the specific challenges encountered there by agents of the church. In Chukotka, the Russian Orthodox Church pursues goals that are simultaneously missionary and political. However, given the combination of difficulties that limit the church’s impact locally, its commitment to establishing its presence in Chukotka is best understood in terms of the strategic importance of the region. Au cours des deux dernières décennies, l’Église orthodoxe russe a promu la construction d'églises et d'autres monuments religieux dans toute la Russie, marquant ainsi le territoire comme orthodoxe. La Tchoukotka, région située à l'extrême nord-est du pays, ne fait pas exception. Cependant, l’effort de construction et d’implantation de l’Église orthodoxe en Tchoukotka est remarquable pour un certain nombre de raisons, qui incluent : l’histoire coloniale de la région, son éloignement de la capitale, sa faible densité de population et ses conditions climatiques extrêmes, ainsi que sa proximité avec les États-Unis. Basé sur des recherches de terrain effectuées en 2018 et sur une expérience de long terme en Tchoukotka depuis 1993, cet article analyse les aspects socio-historiques, ethnographiques et ...